Visitors' attitudes and behavioral intentions toward Leave No Trace on a national forest. Issue 1 (2nd January 2021) - Coulson, Evan; Park, Logan; Lawhon, Ben; Taff, Derrick; Vagias, Wade; Newman, Peter
Abstract: This study examined variables hypothesized to influence behavioral intentions of visitors to frontcountry areas managed by the USDA Forest Service. Data were obtained over a stratified 12-month sampling period ( n  = 281). Analyses revealed that visitor attitudes toward perceived effectiveness of Leave No Trace practices and perceptions of difficulty of practice were statistically significant predictors of behavioral intentions. Forest Service managers may be successful in influencing visitors' behavioral intentions by utilizing communication efforts that focus on the effectiveness of practices, the ease of practice, and the overall appropriateness of practicing Leave No Trace when visiting frontcountry areas.